Hartz IV: The Solution to the Unemployment Problems in the Eurozone? - Peter Bofinger (Intereconomics, 2017)
The Hartz IV reforms are consistently regarded as a successful German model for the reduction of structural unemployment. Is it therefore appropriate to advise other member states of the European monetary union to carry out similar reforms? This paper strongly disagrees, arguing that the reduction in unemployment in Germany since 2005 is mainly due to cyclical factors and to the petering out of the negative employment effects caused by the economic transformation after German unification.
Keywords: 330